Biomarkers of Ovarian Reserve as Predictors of Reproductive Potential - Steiner, Anne Z. (Seminars in Reproductive Medicine, 2013)
The size of the oocyte pool, the ovarian reserve, can determine a woman's reproductive stage. Chronologic age, anti-Müllerian hormone (AMH) levels, early follicular phase follicle-stimulating hormone levels, and early follicular phase inhibin B levels are correlated with ovarian reserve. Therefore, these biomarkers of ovarian reserve should serve as predictors of reproductive potential. Clinical and epidemiologic studies suggest that historical and laboratory biomarkers of ovarian reserve are associated with natural and treatment-related fertility. However, controversy remains as to their ability to predict reproductive potential. For infertile women undergoing assisted reproductive technology treatment, these biomarkers tend to be highly specific but not sensitive for cycle failure (nonpregnancy). While these biomarkers are being used as “fertility tests” in the general population, their value as predictors of unassisted fertility is still uncertain. Among laboratory biomarkers, AMH appears to have the most promise; however, further studies are needed to refine cutoff values and to determine test characteristics in the prediction of natural fertility or infertility in the general population.
Keywords: biomarkers; ovarian reserve; fertility